The Implementation of Punishment Method in Strengthening the Discipline of Students in Islamic Boarding School - Rambe, Mangaraja Sinomba; Noviandi, Riki; Najib, Muh Ainun; Khoirunisa, Tutik; Sopian, Hilmi; Azhari, Novi Nurjannah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aims to explore the implementation of the punishment method as a strategy to strengthen the discipline of students at the Darussalam Parmeraan Islamic Boarding School. This research uses a descriptive qualitative research method through a case study approach related to the implementation of punishment in strengthening student discipline at the Darussalam Parmeraan Islamic boarding school, Dolok sub-district, North Sumatra province. This data collection technique starts with planned observations related to the implementation of punishment to increase the discipline of students. Then, the researcher conducted structured interviews with several teaching staff and student leaders (OSIS), including informants A, B, - N, and informant R. After the data was collected, the researcher would reduce the data, analyze it carefully, and then conclude that it was valid. The research results show that the method of administering punishment has been integrated and applied systematically as the main instrument in building Santri discipline in the Islamic boarding school environment. The Darussalam Parmeraan Islamic Boarding School adapts a balanced approach between educational and humanistic punishments to achieve the goal of developing the character of its students, especially by increasing discipline. The punishment applied to disciplinary violators will be adjusted to the level of error, with a reflection of religious norms and holistic concepts as the main basis for implementing this method of punishment. It can be concluded that punishing violators of regulations is considered very effective as a means of strengthening the discipline of students living their lives in the Islamic boarding school environment. With the existence of rules and consequences, students are more likely to comply with the norms and values that apply in Islamic boarding schools as part of the character education process.